New Magnetic Anomaly Constraints on the Antarctic Crust. Issue 3 (25th March 2022) - Kim, H. R.; Golynsky, A. V.; Golynsky, D. A.; Yu, H.; von Frese, R. R. B.; Hong, J. K.
Abstract: The Antarctic Digital Magnetic Anomaly Project's first‐generation magnetic anomaly map (ADMAP‐1) was produced for the region south of 60°S from about 1.5 million line‐kms of airborne and marine magnetic anomaly data (Golynsky et al., 2001; https://www.bas.ac.uk/data/our‐data/maps/thematic‐maps/admap‐magnetic‐anomaly‐map‐of‐the‐antarctic/ ). The second‐generation ADMAP‐2 compilation (Golynsky et al., 2017; https://doi.org/10.22663/ADMAP.V2 ) incorporated an additional roughly 2.0 million line‐kms of airborne and marine magnetic anomaly data from international mapping through 2015. The present study integrates satellite magnetic observations from the Swarm mission with the near‐surface data of ADMAP‐2 to help fill the regional coverage gaps and better define the altitude behavior of the Antarctic's magnetic anomalies for enhanced geological analysis. The resulting satellite magnetic data‐supplemented compilation, ADMAP‐2s, yields further constraints on the enigmatic geology of the Gamburtsev Subglacial Mountains, Prince Charles Mountains, Wilkes Land, Dronning Maud Land, and other poorly explored Antarctic areas. It offers insights on the global tectonic processes and crustal properties of the Antarctic and helps to unify disparate geologic and geophysical studies by linking widely separated outcrops. It also supports studies on the geological controls of the Antarctic ice sheet, the crustal transitions between Antarctica and the adjacent oceans, and the geodynamic evolution of the Gondwana and Rodinia supercontinents. Plain Language Summary: This study integrates the second‐generation magnetic anomaly compilation with Swarm satellite magnetic data to offer important new constraints on the geology of the Antarctic's crust that is largely hidden beneath a pervasive blanket of seawater, ice, and snow. The satellite data‐supplemented magnetic anomaly compilation links widely separated outcrops to facilitate enhanced understanding of the lithospheric transition between Antarctica and its adjacent oceans, as well as the Antarctic's role in the tectonic evolution of the Gondwana and Rodinia supercontinents. The satellite data‐supplemented magnetic anomaly compilation in combination with complementary geological information, and ice‐probing radar, gravity, and other geophysical data enhances understanding Antarctic crustal rifting, mountain building and basin formation, plate subduction and accretion, and other regional lithospheric processes. Key Points: Swarm satellite magnetic gradient anomaly observations provide useful constraints to help fill regional coverage gaps in the more than 3.5 million line‐km of ship and airborne magnetic anomaly data of the ADMAP‐2 compilation. They also substantially enhance Antarctic crustal studies of the near‐surface magnetic survey data Onshore, the ADMAP‐2 anomalies over West Antarctica include the effects of extensive late Cenozoic volcanic rocks within the West Antarctic Rift System and Mesozoic arc magmatism and terrane accretion along the paleo‐Pacific active margin of Gondwana. Over East Antarctica, they mark the Mawson Craton's southernmost boundary along 85.5°S between 157°E to 135°E to suggest that the Shackleton Ranges may not be part of the craton (Boger, 2011) Offshore, the ADMAP‐2s anomalies illuminate Antarctica's continent‐ocean transition zones. Satellite magnetic anomaly maxima also map enhanced crustal heat flow variations that yield relatively marginal signatures in the near‐surface obserations